Dermatoglyphic Patterns of Finger Tips in the Patients with Pulmonary Tuberculosis - Ahmed, Afrose; Ara, Shamim; Alom, K M Monjurul; Reza, Rumana; Banu, Masuma Akhter (Bangladesh Journal of Anatomy, 2015)
Context: The word dermatoglyphics denotes as the scientific study of the epidermal ridge patterns of fingertips, palm and sole. There are three major classes of dermatoglyphic patterns of finger tips: loops, whorls and arches. Analysis of finger dermatoglyphic is beginning to prove itself as a useful tool for preliminary investigation in conditions with a suspected genetic basis. The genetic contribution is one of the causes of pulmonary tuberculosis. The present study on finger dermatoglyphics pattern was carried out to provide dermatoglyphic as a tool for early prediction of pulmonary tuberculosis by comparing dermatoglyphic patterns of pulmonary tuberculosis patients with the normal healthy individuals. Materials and Methods: A Cross-sectional, analytical type of study was conducted in Department of Anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The study was performed on 100 patients suffering from pulmonary tuberculosis and 100 healthy individuals. Results: The percentage of whorl in pulmonary tuberculosis patients was significantly higher than control group (P<0.001). On the other hand, in pulmonary tuberculosis patients ulnar loop, radial loop and arch were 30.4%, 0.1% and 4.9% respectively and in control group were 72.3% , 2.5% and 10.3% respectively. Ulnar loop, radial loop and arch were significantly decreased in the patients group as compared to controls. Conclusion: In the present study the percentage of whorl was predominantly higher in the pulmonary tuberculosis patient than the control subjects. Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 62-66